STRATIFIKASI SOSIAL DALAM TRADISI RAMPANAN KAPA' PADA MASYARAKAT DI KECAMATAN SA'DAN KABUPATEN TORAJA UTARA - Rusdi Rusdi; Elsa Juliana; Feri Padli (Humano: Jurnal Penelitian, 2023)
This study aims to determine the meaning of the rampanan kapa' tradition and the factors that encourage the emergence of social stratification and its impact on the implementation of the rampanan kapa' tradition in Sa'dan District, North Toraja Regency. This study uses qualitative research methods with observation techniques, in-depth interviews, and in-depth analysis to obtain the desired data. Interviews were conducted with several informants who had knowledge and had participated in carrying out or participating in the Kapa' Rampanan tradition. The results of this study indicate that: (1) Rampanan Kapa' for the Sa'dan people is interpreted as a traditional procession, starting from at least a statement of intent from the groom, ussorong food, discussing the time and place of the proposal, and ma parampo (application procession). (2) The factors that encourage the emergence of social stratification in the Rampanan Kapa' tradition in the Toraja people in Sa'dan District are divided into 4 factors, namely heredity, education, wealth, and position. Hereditary factor is the main indicator of this determination. While other factors are only a support. (3) The impact of social stratification affecting the implementation of the Kapa' Rampanan tradition in the Toraja people in Sa'dan District affects 3 aspects of position, rules, and sanctions. In the position of the tradition, the rampanan kapa' is divided into 3, namely rampo bongi for the lower strata, rampo karoen for the middle class and rampo allo for the highest strata. The rules for carrying out the Kapa' Rampanan tradition at the highest stratification are all the sequences in the Kapa' Rampanan procession which are permitted to be carried out. As for the sanctions, if one of the parties violates after the marriage, they will be subject to sanctions in accordance with what was agreed upon at the time of application.